PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN PELATIHAN TERHADAP KINERJA PEGAWAI DI KANTOR DISTRIK BINTUNI KABUPATEN TELUK BINTUNI - Abner Naa (Jurnal Renaissance, 2017)
This research to analyze about how much the influence of the working influence, motivation work and training to the employee performance at the Bintuni District Office of the Teluk Bintuni Regency. This research using the quantitative approach with the explanatory survey method used the quetioner. Variable of this research are the working environment variable (X1), motivation work variable (X2), training variable (X3) to employee performance (Y). The amount of population are the whole of employee, that’s are Civil Servant and Honorer amounted 31 employees working at the Bintuni District Office so that become the respondent in this research. The data collection technique with the quetioner using of Likert scala to examining validity and reliability.  The resulst of this research showed that the working environment made strong influence to the employee performance showing to the correlation of coeficien is 0,662 and determination of coefisien is 0,438. The motivation work have strong influence to the employee performance with the correlation value is 0,667 and the determination of coeficien is 0,458. The training have a low influence with the correlation of coeficien is 0,606 and the determination of coeficien is 0,36. The working environment, motivation work and training with together have a strong influence to the employee performance with the determination is 0,667. Analysis of this research find out that the working environment and motivation work have a strong influence than the training have a low influence to employee performance at the Bintuni District Office of the Teluk Bintuni Regency.Key words:  working           environment,        motivation            work, training, employee performance